Mixed methods social network analysis theories and methodologies in learning and education - Froehlich, Dominik E.; Rehm, Martin; Rienties, Bart C. (Routledge, Taylor & Francis Group, 2020)
Mixed methods social network analysis brings together diverse perspectives from 42 international experts on how to design, implement, and evaluate mixed methods social network analysis (MMSNA). There is an increased recognition that social networks can be important catalysts for change and transformation.